Bibliography of Ethiopian Semitic, Cushitic and Omotic Linguistics XXII: 2018 - Bulakh, Maria; Hummel, Susanne; Panini, Francesca (Aethiopica, 2019)
Bibliography of Ethiopian Semitic, Cushitic and Omotic Linguistics XXII: 2018